In situ disappearance speed of a hard molasses block on low quality forage. Technical note - Ascanio, G. N. D.; Elías, A.; Santini, F.; Herrera, F. (Cuban Journal of Agricultural Science, 2018)
The objective of this study was to determine the disappearance and the disappearance speed of whole hard molasses blocks in the rumen of cannulated cows fed with low quality hay. Three cows in a completely randomized design were used. Tubular plastic mesh bags, with hole size of 3 mm were used with 100 g of hard molasses blocks, incubated in the dorsal sac of rumen during different fermentation times: 30, 60, 120, 240 and 480 min. The fraction of disappearance to the wash was 2.57 %. The average disappearance speed was 213 mg.min-1 and was fitted next to D, a quadratic polynomial regression model (R2=0.67and 0.95, respectively), in which it reached a maximum value at 480 min (76.4 %). The remainder of 23.4 % corresponds to a particle size between 4 and 7 mm. It is concluded that the hard molasses blocks achieve a slow release of their components over time, finding material in the rumen of the cannulated cows still at 480 min of incubation.Key words: forage, block, molasses